Hydrographic data from the GEF Patagonia cruises - Charo, M. (2014)
The hydrographic data reported here were collected within the framework of the Coastal Contamination, Prevention and Marine Management Project (Global Environment Facility (GEF) Patagonia), which was part of the scientific agenda of the United Nations Development Program (UNDP). The project goal was to strengthen efforts to improve sustainable management of marine biodiversity and reduce pollution of the Patagonia marine environment. The observational component of the project included three multidisciplinary oceanographic cruises designed to improve the knowledge base regarding the marine environment and to determine the seasonal variability of physical, biological and chemical properties of highly productive regions in the southwest South Atlantic continental shelf. The cruises were carried out on board R/V ARA Puerto Deseado, in October 2005 and March and September 2006. On each cruise, hydrographic stations were occupied along cross-shelf sections spanning the shelf from nearshore to the western boundary currents between 38◦ and 55◦ S. This paper reports the quasi-continuous vertical profiles (conductivity–temperature–depth (CTD) profiles) and underway surface temperature and salinity data collected during the GEF Patagonia cruises.